THE INFLUENCE PHYSICAL WORK ENVIRONMENT AND LEADER MEMBER EXCHANGE ON TURNOVER IN THE FLOOR DIVISION OF PT. MIDI UTAMA INDONESIA TBK (CAB. MEDAN) - Pohan, Yuli Arnida (Jurnal Manajemen Bisnis Eka Prasetya, 2025)
Turnover is a situation where there is an intention or action of an employee to quit and leave his job. Poor turnover rates can be a serious problem for an organization or company. The purpose of this study was to determine the effect of physical work environment and leader member exchange on employee turnover both simultaneously and partially at PT. Midi Utama Indonesia Tbk (Cab. Medan). Respondents in this study were all employees of the floor division at PT. Midi Utama Indonesia Tbk (Cab. Medan) as many as 121 employees. The sampling technique in this study using saturated samples. This research uses quantitative descriptive methods. The research results of the research obtained that turnover has a positive and significant effect on the physical work environment and turnover has a positive and significant effect simultaneously on leader member exchange.